PERBANDINGAN BOBOT BADAN KAMBING PERANAKAN ETAWA YANG TERINFESTASI CACING SALURAN PENCERNAAN - Madi Hartono; Purnama Edy Santosa; Muhammad Mirandy Pratama Sirat (JURNAL ILMIAH PETERNAKAN TERPADU, 2018)
Worm disease is a disease caused by infestation of worms in the body of animals with minimal risk to cause death, but causes losses in the form of decreased body weight, milk production, body resistance to other diseases and stunted growth, especially goats at a young age. Population of goats in Lampung Province is the third largest position in Indonesia that it is important to know the effects that can be caused due to intestinal worms. The purpose of this study was to determine the ratio of goat body weight infestated by various types of intestinal worms so that the researchers knew the impact of digestive tract worms infestation on goat body weight. The study was conducted in the period July - October 2018 in the Budi Lestari Livestock Group, Gedong Tataan, Pesawaran Regency, Lampung Province. The type of goat used in the study was the Etawa Breeders Goat. The method is a completely randomized design (CRD) with five treatments, namely the group of uninfested goats (P1); goat infested with 1 type of worm (P2); goat infested with 2 types of worms (P3); goats infected with 3 types of worms (P4); and goats infected with 4 types of worms (P5). Implementation procedures were (1) conducting a survey of PE goat populations; (2) Determining the age of PE goats; (3) Taking feces; (4) Identifying worm eggs (Mc Master Test and Sedimentation Test); (5) Determine samples; (6) Considering body weights; (7) Data tabulation and analysis. Data analysis was carried out using One Way Analysis of Variance (ANOVA) method at a 95% confidence level with SPSS 24 software program, if there were significant differences then proceed with the Least Significant Differences (LSD) and Duncan Test. The results of the data analysis showed that there were no significant differences between treatments (p> 0.05), but based on the average data of PE goats body weight from various treatments the highest in the treatment group that did not infest worm infestation (P1) was 25.25 kg, continued to decline respectively P2 (19.00 kg), P3 (18.25 kg), P4 (16.00 kg), P5 (15.25 kg). The conclusion of the study is the more types of worm infestations in the body, the lower of PE goats body weight. Keywords: Body Weight, Etawa Breed Goat, Infestation, Intestinal Worms, Types of Worm